Linguistic and Content Features of Article Titles Published in Local & High-Impact Foreign Journals in English Education : How Are They Similar and Different? - Arsyad, Safnil; Ramadhan, Syahrul; Hakim, Husnul (Jurnal Arbitrer, 2024)
Journal article titles serve as both the introduction to the substance of articles and incentives for users to read articles in their entirety, but different quality articles may use different linguistic and content features of titles. This is rarely investigated by discourse analysts. The goal of this research is to compare and contrast titles in the English education field written by Indonesian authors and published in local journals with those written by foreign authors and published in high-impact foreign journals. Two hundred and eight article titles from five different Indonesian-accredited local journals and 512 article titles from five different high-impact foreign journals form the corpus of this research. The analyses were done on the titles' length and their linguistic and content features. The findings show that the article titles in high-impact foreign journals are slightly longer than those in local journals, local authors use nominal construction and verb-ing phrase types more frequently than high-impact foreign authors do, foreign authors use full sentences and prepositional phrases more frequently than the local journal authors do, and high-impact foreign journals use topic-only type of titles more frequently than in local journals do. The similarities are that nominal and compound constructions are the most dominant linguistic features while topic-only and method categories are the most dominant content features in both groups of article titles. While the most important features of titles are probably the conciseness and preciseness of the information contained in the titles, future studies should investigate these aspects of journal article titles in the same or different fields.